Impact of semen insemination on the vaginal microbiome profile of candidiasis rat model: A preliminary forensic study on sexual violence evidence - Iswara, Raja AFW.; Hestiantoro, Andon; Budiningsih, Yuli; Werdhani, Retno A.; Birowo, Ponco; Wuyung, Puspita E.; Fadilah, Fadilah; Afandi, Dedi (Narra J, 2025)
Sexual violence, including sexual intercourse, can occur in women experiencing vaginal discharge, particularly in cases of vaginal candidiasis. In candidiasis, the vaginal microbiome undergoes changes that could serve as a diagnostic indicator or as evidence of sexual activity.  The aim of this study was to assess the effects of semen insemination on the vaginal microbiome profile of candidiasis rats and to determine its forensic investigations in cases of sexual violence.  An experimental study was carried out using Wistar strain rats (Rattus norvegicus), consisting of four male rats (for spermatozoa donors) and twenty-four female rats. The female rats were divided into four groups: normal condition (control), normal condition post-semen insemination, candidiasis rats, and candidiasis rat post-semen insemination. Vaginal microbiome profiles were examined for each group, using alpha diversity (Chao 1, Shannon, Simpson, and Faith PD indices) and beta diversity (Bray Curtis, Jaccard, Unweighted Unifrac and Weighted Unifrac indices). Data were analyzed using the Kruskal-Wallis test for alpha diversity and the PERMANOVA test for beta diversity. The vaginal microbiome profiles of normal and candidiasis rats showed no significant differences (p>0.05). In candidiasis rats, the microbiome predominantly consisted of the Eukaryota kingdom, particularly Candida albicans. Semen insemination did not significantly affect the vaginal microbiome profile of candidiasis rats in the short term (p>0.05). However, the study highlights that the presence of Eschericia-Shigella, Roseomonas, and Archaea in the vaginal microbiome post-semen insemination potentially serves as an indicator of infection or sexual activity in forensic contexts.